QiDiTangShen Granules Activate Renal Nutrient-Sensing Associated Autophagy in db/db Mice - Wang, Xiangming; Zhao, Li; Ajay, Amrendra K.; Jiao, Baihai; Zhang, Xianhui; Wang, Chunguo; Gao, Xue; Yuan, Zhongyu; Liu, Hongfang; Liu, Wei Jing (Frontiers in Physiology, 2019)
QiDiTangShen granules (QDTS) have been proven to reduce the proteinuria in patients with diabetic nephropathy (DN) effectively. The present study was aimed to investigate the mechanism underlying QDTS’s renoprotection. The main components of QDTS were identified by ultra-high liquid chromatography-tandem mass spectrometry and pharmacological databases, among which active components were screened by oral bioavailability and drug-likeness. Their regulation on autophagy-related nutrient-sensing signal molecules (AMPK, SIRT1, and mTOR) was retrieved and analyzed through the Pubmed database. Then, db/db mice were randomly divided into three groups (model control, valsartan and QDTS), and given intragastric administration for 12 weeks, separately. Fasting and random blood glucose, body weight, urinary albumin excretion (UAE) and injury markers of liver and kidney were investigated to evaluate the effects and safety. Renal histological lesions were assessed, and the expressions of proteins related to nutrient-sensing signals and autophagy were investigated. Thirteen active components were screened from 78 components identified. Over half the components had already been reported to improve nutrient-sensing signals. QDTS significantly reduced UAE, ameliorated mesangial matrix deposition, alleviate the expression of protein and mRNA of TGF-β, α-SMA, and Col I, as well as improved the quality of mitochondria and the number of autophagic vesicles of renal tubular cells although the blood glucose was not decreased in db/db mice. Compared to the db/db group, the expression of the autophagy-inducible protein (Atg14 and Beclin1) and microtubule-associated protein 1 light chain 3-II (LC3-II) were up-regulated, autophagic substrate transporter p62 was down-regulated in QDTS group. It was also found that the expression of SIRT1 and the proportion of p-AMPK (thr172) / AMPK were increased, while the p-mTOR (ser2448) / mTOR ratio was decreased after QDTS treatment in db/db mice, which was consistent with the effect of its active ingredients on the nutrient-sensing signal pathway as reported previously. Therefore, QDTS may prevent the progression of DN by offering the anti-fibrotic effect. The renoprotection is probably attributable to the regulation of nutrient-sensing signal pathways, which activates autophagy.